The Role of Monetary Policy in Supporting Green Economic Growth: Opportunities and Challenges for the Indonesian Central Bank - Sylvia, Sylvia (Economics Monetary Journal, 2025)
The transition to a green economy is a strategic agenda in sustainable development that requires support from various sectors, including the monetary sector. Amid the increasing urgency of climate change mitigation, the central bank's role in integrating sustainability principles into its monetary policy is becoming increasingly relevant. This research aims to analyze the opportunities and challenges of monetary policy in supporting green economic growth, focusing on Bank Indonesia's readiness as a national monetary authority. The approach used is qualitative descriptive with case study methods and thematic and policy analysis techniques. Data were obtained from literature reviews, policy documents, and national and international institutional reports. The results show that although Bank Indonesia has a strategic role in supporting the transformation of the green economy, there are currently no monetary instruments specifically directed to environmental purposes. Limited legal mandates, the unavailability of a green classification framework, and weak coordination between institutions are the main obstacles. This study recommends the reformulation of institutional mandates, the development of green monetary instruments such as green refinancing and differential interest rates, and the establishment of a dedicated unit for climate risk analysis. These findings underscore the importance of integrating sustainability aspects into monetary policy as part of efforts to create sustainable long-term economic stability.